2020
DOI: 10.1111/1759-7714.13544
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus distinguishes second primary tumors from lung metastases in patients with squamous cell carcinoma of the cervix

Abstract: Background: In patients with squamous cell carcinoma of the cervix (SCCC), a squamous cell carcinoma (SqCC) in the lung represents either a second primary tumor or metastasis. This distinction between second primary tumors and lung metastases in patients with SCCC significantly influences patient prognosis and therapy. Here, we aimed to differentiate second primary tumors from lung metastases in patients with SCCC by exploring the HPV status in SqCCs involving the lung within a large cohort. Methods: P16 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…Interestingly, HPV-negative samples showed p16 RNAm expression but not protein expression, 9 Cellular Microbiology which indicates that some type of posttranscriptional regulation of p16 is happening, such as microRNA binding to p16 RNAm [58]. Therefore, our results indicate that p16 may have an important value in distinguishing HPV-infected lung cancer tissues, which differs from other studies where no association was found between p16 and HPV in lung cancer samples [15,18].…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, HPV-negative samples showed p16 RNAm expression but not protein expression, 9 Cellular Microbiology which indicates that some type of posttranscriptional regulation of p16 is happening, such as microRNA binding to p16 RNAm [58]. Therefore, our results indicate that p16 may have an important value in distinguishing HPV-infected lung cancer tissues, which differs from other studies where no association was found between p16 and HPV in lung cancer samples [15,18].…”
contrasting
confidence: 82%
“…However, the well knows the relation between HPV and p16 in cervical cancer might not be the same in lung cancer. Not all patients infected with HPV and expressing its oncoproteins have an expressively change in p16 expression, and some studies did not find an association between HPV and p16 expression, as is the case in cervical cancer [15][16][17][18]. In any case, p16 positivity showed significant prognostic usefulness in non-small lung cancer patients, but its association with HPV in lung cancer still needs further study [19].…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, the oncoprotein HPV E6/E7 gene expression could be the most accurate evaluation for such cases. [10][11][12] Therefore, these studies show remarkably low evidence of the involvement of HPV in primary lung cancer.…”
Section: Discussionmentioning
confidence: 88%
“…Despite this, p16 is overexpressed not only by HPV E7‐induced pRB inactivation but also by other factors, including mutations in cell cycle regulators CDK4 and CDK6, inflammation, ageing and stress 6,7 . Several studies have shown that p16 is overexpressed in patients with non‐small cell lung cancer 8–10 . In cervical SCC, p16 is uniformly strongly and diffusely expressed in tumour cells, 4 whereas in non‐small cell lung cancer, p16 expression is uneven and variable 8–10 .…”
Section: Discussionmentioning
confidence: 99%
“…For example in one large study of 42 cases, high-risk HPV was detected in 85.7% of cervical NEC, predominantly HPV 16 (54.8%) followed by HPV 18 (40.5%) (15). One important point to note is that although block-type p16 staining is a surrogate marker of the presence of high-risk HPV, diffuse blocktype p16 staining is not uncommon in HPV-negative NEC arising at other sites such as the lung and head and neck region (21,22).…”
Section: Discussionmentioning
confidence: 99%